Islamic Religious Management of Students at SMP Muhammadiyah 1 Ngawi - Satria Arif Wicaksono; Hafidz (al-Afkar, Journal For Islamic Studies, 2024)
Islamic religious management in an educational environment plays a crucial role in shaping the character and morality of students. This research aims to analyze and describe the Islamic religious management of students at SMP Muhammadiyah 1 Ngawi. The research method used is descriptive with a qualitative approach. Data were collected through observation, interviews, and documentary studies. The results show that Islamic religious management at SMP Muhammadiyah 1 Ngawi involves various aspects, such as religious curriculum, moral development, religious activities, and student involvement in Islamic activities. The religious curriculum is designed to cover the understanding of Islamic concepts, Quranic learning, and worship practices. Moral development is conducted through student guidance, setting examples, and group mentoring. Religious activities in the school include group prayers, religious studies, and other religious events. Students are encouraged to actively participate in Islamic activities, both within and outside the school. The involvement of students in these Islamic activities is expected to shape Islamic character and strengthen students' religious identity. Islamic religious management at SMP Muhammadiyah 1 Ngawi emphasizes the integration of formal education and religious education, enabling students to develop a holistic understanding of Islam. This research provides an overview of the school's efforts to shape morally upright and Islamic-identifying students, contributing positively to the development of Islamic religious education at the junior high school level.